(untitled) (Journal of Namibian Studies : History Politics Culture, 2024)
Political brand hate is a socio-psychological praxis in which former fervid party supporters develop intensely adverse hatred towards a political party they formerly loved resulting in negative outcomes such as party ambivalence, rejection, party switching and even nihilism. The motive of this paper was to examine the antecedents for political party brand hate in Zimbabwe. Combining marketing and political science knowledge domains, the study used a multinomial regression equation with three dependent variables: political party hate, political party love and political party indifference. Systematic sampling was used to collect quantitative data from 100 supporters of Zimbabwe’s two main political parties. Our findings show that ideological incompatibility, image incongruity, moral self-concept, party betrayal and self-incongruity are key factors in inducing the probability of political party brand hate. Core service offerings that attract political consumers include political ideology, public expenditure management, socio-economic policies and programs. Political parties in Zimbabwe are urged to negative anti-brand strategies such as party arrogance, voter-party incompatibility and breach of pre-election promises in order to increase party brand love. The contribution of the paper to research lies in pioneering the use of multinomial logit regression equation to integrate political and marketing disciplines to study political issues in Zimbabwe.